27 Greenhouse Gas Emissions and a Partial Life Cycle Assessment When Growing Pigs Are Fed High Wheat Millrun Diets. (7th May 2021) - Kpogo, Agbee L; Jose, Jismol; Panisson, Josiane; Predicala, Bernardo; Alvarado, Alvin; Agnew, Joy; Sprenger, Charley; Beaulieu, Denise A
Abstract: The impact of feeding growing pigs with high wheat millrun diets on the global warming potential (GWP) of pork production was investigated. In study 1, a 2 × 2 factorial arrangement of wheat millrun (0 or 30%) and multi-carbohydrase enzyme (0 or 1 mg kg -1 ) as main effects was utilized. For each of 16 reps, 6 pigs (60.2±2.2 kg BW) were housed in environmental chambers for 14d. Air samples were collected and analyzed for carbon dioxide (CO2 ); nitrous oxide (N2 O); and methane (CH4 ). In study 2, data from study 1 and performance data obtained from a previous feeding trial were utilized in a life cycle assessment (LCA) framework that included feed production. The Holos farm model (Agriculture and Agri-Food Canada, Lethbridge. AB) was used to estimate emissions from feed production. In study 1, total manure output from pigs fed 30% wheat millrun diets was 30% greater than pigs on the 0% wheat millrun diets (P < 0.05), however, Feeding diets with 30% millrun did not affect greenhouse gas (GHG) output (CH4, 4.7, 4.9; N2 O, 0.45, 0.42; CO2, 1610, 1711; mg s -1 without or with millrun inclusion, respectively; P > 0.78). Enzyme supplementation had no effect on GHG production (CH4, 4.5, 5.1; N2 O, 0.46, 0.42; CO2, 1808, 1513; mg s -1 without or with enzymes, respectively; P > 0.51). In study 2, the LCA indicated that the inclusion of 30% wheat millrun in diets for growing pigs resulted in approximately a 25% reduction in GWP when compared to the no wheat millrun diets. Our results demonstrate that 30% wheat millrun did not increase GHG output from the pigs, and thus the inclusion of wheat millrun in diets of growing pigs can reduce the GWP of pork production.